Molecular design opening two emission pathways for high efficiency and long lifetime of thermally activated delayed fluorescent organic light-emitting diodes. Issue 23 (2nd June 2021) - Lee, Ha Lim; Lee, Kyung Hyung; Lee, Jun Yeob; Lee, Ho Jung
Abstract : High efficiency and long lifetimes of thermally activated delayed fluorescent organic light-emitting diodes were developed using a novel molecular design with two emission pathways. Abstract : High efficiency and long lifetimes of thermally activated delayed fluorescent (TADF) organic light-emitting diodes (OLEDs) were developed using a novel molecular design with two emission pathways for a high photoluminescence quantum yield and high reverse intersystem crossing rate. The new TADF molecular design had one donor and two acceptors at ortho and para -positions to the donor in the phenyl linker. The acceptor para to the donor mainly increased the photoluminescence quantum yield, whereas the acceptor ortho to the donor predominantly improved the reverse intersystem crossing rate. As a result, the TADF emitters with the two acceptor chemical platforms achieved high external quantum efficiency of over 20% and a lifetime longer than that of the state of the art TADF device.